The poverty of Clio: resurrecting economic history - Boldizzoni, Francesco (Princeton University Press, 2011)
The Poverty of Clio challenges the hold that cliometrics--an approach to economic history that employs the analytical tools of economists--has exerted on the study of our economic past. In this provocative book, Francesco Boldizzoni calls for the reconstruction of economic history, one in which history and the social sciences are brought to bear on economics, and not the other way around.